NORBOTABIY MADRASAH (ResearchJet Journal of Analysis and Inventions, 2021)
This article provides information about the history of the construction of the Norbotabiy madrasah in Kokand, its location, and the masters involved in its construction. The existing education system in Kokand in the XVIII-XIX centuries is covered in detail.